The power of the centre : central governments and the macro-implementation of EU public policy - Dimitrakopoulos, Dionyssis G., 1969- (European Policy Research Unit series., 2017)
This book, newly available in paperback, examines a hitherto under-researched aspect of the European Union's policy process - the extent and the nature of the involvement of central governments in the implementation of EU public policy. It discusses how the co-ordination of these institutions affects their capacity to shape the way in which the commitments that they make in Brussels are turned into concrete reality at the national level. It shows that the nature of their involvement in implementation reflects the pattern of their involvement in the formulation of EU policy. However, since imple.